ANALISIS MINAT BELAJAR SISWA KELAS III SD NEGERI WONOSARI KECAMATAN NGOMBOL KABUPATEN PURWOREJO - Susi Widia Astuti; Heru Purnomo (Elementary School Teacher Education (PGSD), STKIP PGRI Sumenep, 2023)
This study aims to determine the learning interest of third grade students at SD Negeri Wonosari, Ngombol District, Purworejo Regency. The method used in this study is a qualitative method and is presented in a descriptive form. The technique used to obtain information in this study was an interview technique with the object of the interview, namely students' interest in learning and the subject of the interview, namely class III teaching staff and class III students, and the interview was held on May 13, 2023 at SD Negeri Wonosari, Ngombol District, Kabupaten Purworejo. And the results of the interviews were analyzed and presented in a descriptive form. The interviews referred to 4 indicators of interest in learning namely: feeling happy, interested in learning, showing attention while studying and involvement in learning. From the results of the interviews it is known that students do not have a full feeling of pleasure in learning; students are less interested in learning because the teacher has not used monotonous media and learning methods; students have not shown their full attention in learning, there are still many students who are busy chatting, busy, and walking around during learning; and students are still slightly involved in learning. The results of the research lead to low student interest in learning caused by several factors such as: motivation, facilities, learning methods, and the environment. Teachers must try to develop students' interest in learning so that learning is achieved optimally.